Modeling 3‐D artificial ionospheric ducts. Issue 11 (26th November 2013) - Zawdie, K. A.; Huba, J. D.; Wu, T.‐W.
<x xml:space="preserve">Abstract</x> [1] The injection of powerful HF waves into the ionosphere leads to strong electron heating followed by a pressure perturbation, which can drive electrons along the field line to the conjugate side, creating what is known as an artificial duct. The electron temperature along the duct is above the ambient temperature; the electron density is depleted on the heating side and increased on the conjugate side. Duct formation due to HF heating has previously been studied using a modified version of SAMI2 (Sami2 is Another Model of the Ionosphere). We use a similarly modified version of SAMI3 to examine the effects of zonal E × B drifts on interhemispheric ducts created by heating over Arecibo. We found that the longitudinal E × B drifts, particularly those caused by the zonal neutral winds, significantly suppress the effects of HF heating on the conjugate side, reducing the temperature and density increases by about 90% and 75%, respectively.